Spinal Instrumentation Rescue with Cement Augmentation - Cianfoni, A.; Giamundo, M.; Pileggi, M.; Huscher, K.; Shapiro, M.; Isalberti, M.; Kuhlen, D.; Scarone, P. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Altered biomechanics or bone fragility or both contribute to spine instrumentation failure. Although revision surgery is frequently required, minimally invasive alternatives may be feasible. We report the largest to-date series of percutaneous fluoroscopically guided vertebral cement augmentation procedures to address feasibility, safety, results and a variety of spinal instrumentation failure conditions.MATERIALS AND METHODS: A consecutive series of 31 fluoroscopically guided vertebral augmentation procedures in 29 patients were performed to address screw loosening (42 screws), cage subsidence (7 cages), and fracture within (12 cases) or adjacent to (11 cases) the instrumented segment. Instrumentation failure was deemed clinically relevant when resulting in pain or jeopardizing spinal biomechanical stability. The main study end point was the rate of revision surgery avoidance; feasibility and safety were assessed by prospective recording of periprocedural technical and clinical complications; and clinical effect was measured at 1 month with the Patient Global Impression of Change score.RESULTS: All except 1 procedure was technically feasible. No periprocedural complications occurred. Clinical and radiologic follow-up was available in 28 patients (median, 16 months) and 30 procedures. Revision surgery was avoided in 23/28 (82%) patients, and a global clinical benefit (Patient Global Impression of Change, 5–7) was reported in 26/30 (87%) cases at 1-month follow-up, while no substantial change (Patient Global Impression of Change, 4) was reported in 3/30 (10%), and worsening status (Patient Global Impression of Change, 3), in 1/30 (3%).CONCLUSIONS: Our experience supports the feasibility of percutaneous vertebral augmentation in the treatment of several clinically relevant spinal instrumentation failure conditions, with excellent safety and efficacy profiles, both in avoidance of revision surgery and for pain palliation.PGICPatient Global Impression of ChangePMMApolymethylmethacrylate